Faces of Precarity Critical Perspectives on Work, Subjectivities and Struggles (Bristol Bristol University Press, 2022)
The digital PDF of the Introduction, Chapter 3, Chapter 8 and the Afterword of this title are available Open Access under CC-BY-NC-ND licence. The word 'precarity' is widely used when discussing work and employment, social conditions and lived experiences, and social classes. There is not, however, a consensus on the precise meaning of the term or how it should best be used to explore social changes. Bringing together an international group of thinkers from a diverse range of fields, this book offers a distinctive and critical perspective approach to an important topic.
English
Keywords: Personnel and human resources management; Political economy; Contingency; Critical; Employment; Insecurity; Platform economy; Social class; Social conditions; Temporary work